Prevalensi dan Faktor Risiko Anemia pada Anak di Negara Maju - Izzania Oktaviani; Desie Rahmawati; Yulianti Nataya Rame Kana (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: Anemia is a global public health problem that occurs in developed countries or in developing countries. The prevalence of anemia in children aged 1-5 years in the United States is 3.9% and iron anemia is 1.1%. This review discussed prevalence and the risk factors and anemia in children in developed countries. Method: The method used is a literature review, the data source in the form of research articles is obtained from online databases, namely Google Scholar and Science Direct. The articles reviewed were 10 articles that met the inclusion criteria. Result: Based on several studies, iron deficiency or deficiency is the most common cause in children in developed countries. 8% of children under five in the United States have iron deficiency, and 2-3% of them are iron deficiency anemia. Risk factors for anemia include lack of serum zinc, low levels of 25 (OH) D, exclusive breastfeeding without iron fortification, Low Birth Weight (LBW), food intake factors, history of asthma and eczema, and maternal education. Iron deficiency anemia in childhood has been shown to have a negative effect on cognitive and psychomotor development. Prevention of anemia that can be done include giving iron supplements and food recommendations. Conclusion: Risk factors for anemia include lack of serum zinc, low 25 (OH) D levels, exclusive breastfeeding without iron fortification, Low Birth Weight (LBW), food intake factors, history of asthma and eczema, and maternal education.